Restatement terhadap Unsur Perencanaan dalam Pasal 340 KUHP - Arifin Andiwewang; Moonti, Roy Marthen; Ahmad, Ibrahim (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Article 340 of the Indonesian Criminal Code (KUHP) regulates the crime of premeditated murder, which is characterized by the element of “with prior planning”. This element serves as the principal distinction between ordinary murder and premeditated murder. However, in judicial practice, this element is often interpreted inconsistently by judges, potentially resulting in disparities in verdicts and injustice in criminal adjudication. This research aims to restate and clarify the meaning of “prior planning” in Article 340 KUHP to promote a more consistent and fair application of the law. The research employs a normative juridical approach by analyzing a number of court decisions from the Kotamobagu District Court related to premeditated murder cases. The theoretical framework includes sentencing theory as the grand theory, legal interpretation theory as the middle theory, and criminal responsibility theory as the applied theory. The findings reveal inconsistencies in how judges assess the element of “planning”, particularly regarding the psychological state of the perpetrator and the existence of a cooling-down period between intention and execution. Based on these findings, a more explicit and standardized formulation of the term “prior planning” is necessary to ensure proportional legal enforcement, legal certainty, and substantive justice in applying Article 340 KUHP.